Role of Bisphosphonates in The Prevention of Postoperative Hungry Bone Syndrome in Primary Hyperparathyroidism: A Meta-Analysis and Need for Randomized Controlled Trials - Pal, Rimesh; Gautam, Akanksha; Bhadada, Sanjay Kumar (Drug Research, 2020)
Dear Editor,Hungry bone syndrome (HBS) is a clinico-biochemical entity characterized by the development of profound and prolonged hypocalcemia associated with hypophosphatemia, hypomagnesemia, and rising alkaline phosphatase which follows curative parathyroidectomy for severe primary and secondary hyperparathyroidism. The prevalence of HBS after parathyroidectomy in primary hyperparathyroidism (PHPT) is variable with several case series from Asia reporting remarkably higher prevalence rates of 24–87% 1.